2009
DOI: 10.1186/cc7824
|View full text |Cite
|
Sign up to set email alerts
|

Delayed admission to the ICU increases mortality in septic shock

Abstract: Introduction Many authors have written about the need to treat patients closer to their beds, in order to observe them more as distinct people. The FAST HUG mnemonic, which consists of a checklist, was suggested as an idea to be employed everyday, by professionals dealing with patients who are critically ill. Minding these questions and motivated by an idea of follow patients' treatment closer, we have put into practice the instrument developed by Jean-Louis Vincent, evaluating the seven most important procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…There are only few studies that investigated the ICU transfer time in the sepsis population. An observational study in Brazil showed that almost half of the delayed ICU admission with septic shock comes from the ED [24]. Another study suggests a 10% increase in mortality in each day of delayed ICU transfer of severely ill septic patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies that investigated the ICU transfer time in the sepsis population. An observational study in Brazil showed that almost half of the delayed ICU admission with septic shock comes from the ED [24]. Another study suggests a 10% increase in mortality in each day of delayed ICU transfer of severely ill septic patients [25].…”
Section: Discussionmentioning
confidence: 99%